1998
DOI: 10.5271/sjweh.289
|View full text |Cite
|
Sign up to set email alerts
|

Variability in skin exposure in machine operators exposed to cutting fluids

Abstract: Variability in skin exposure in machine operators exposed to cutting fluids by Wassenius O, Järvholm B, Engström T, Lillienberg L, Meding B Key terms: hand eczema; occupation; skin exposure This article in PubMed: www.ncbi.nlm.nih.gov/pubmed/9630060 Scand J Work Environ Health 1998;24(2): 125-9 Variability in the skin exposure of machine operators exposed to cutting fluids by Ola Wassenius, MSG,' Bengt Jarvholm, MD,* Tomas Engstrom, PhD,' Linnea Lillienberg, PhD,3 Birgitta Meding, MD4 Wassenius 0, Jarvh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
(2 reference statements)
1
7
0
Order By: Relevance
“…The authors found that a shorter cycle time was related to increased skin wetness. We found an association between the numbers of work pieces handled with dermal exposure for workers using compressed air to clean work pieces, which is in congruence with the relation found by Wassenius and colleagues 15 for cycle time, as machines with shorter cycle times generally result in a higher number of work pieces handled by a worker. In addition, we found different dermal exposure levels for open and closed machines, but not for different types of closed machines, whereas Wassenius and colleagues 15 did not find any relation between type of machine and skin wetness.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The authors found that a shorter cycle time was related to increased skin wetness. We found an association between the numbers of work pieces handled with dermal exposure for workers using compressed air to clean work pieces, which is in congruence with the relation found by Wassenius and colleagues 15 for cycle time, as machines with shorter cycle times generally result in a higher number of work pieces handled by a worker. In addition, we found different dermal exposure levels for open and closed machines, but not for different types of closed machines, whereas Wassenius and colleagues 15 did not find any relation between type of machine and skin wetness.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, we found different dermal exposure levels for open and closed machines, but not for different types of closed machines, whereas Wassenius and colleagues 15 did not find any relation between type of machine and skin wetness. Possibly, machinery studied by Wassenius and colleagues 15 did not include open machines, or differences between open and closed machines are less adequately detected by observational methods. The latter can also be seen from our study because, as compared to the quantitative dermal exposure assessment methods, the DREAM method detected a smaller, not statistically significant, difference in exposure levels between open and closed machines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such methods are, however, not feasible in epidemiological studies. Videotape recording has been used for measuring skin exposure to cutting fluids (3). Some studies have tried to quantify the time of skin exposure through questionnaires (4, 5) and observations (6, 7).…”
mentioning
confidence: 99%
“…Dermal contact during occupational activities involving hand manipulations during liquid applications—such as application of biocides, or work with semisynthetic metal working fluids (i.e., products used as lubricants and coolants during the machining or treatment of metal components)—tends to be measured in units of cumulative mass contacted or potential flux (as mass per cm 2 /h), rather than in terms of areas and/or durations of liquid contact per se , with results that exhibit substantial magnitudes of interindividual variability . Only a percentage equal to 100(f T wet )% of total parts washing duration T was assumed to generate MSS exposure by either Process 1 or 2, where f T wet was estimated to be 100% for T < 10 minutes and 50% for T ≥ 10 minutes, based on field observations indicating that durations of wet‐hand contact for manual work involving the use of liquids do not typically exceed 50% . Of the total of the wet duration (f T wet T ), only an uncertain fraction (f T splash ) was assumed to involve brushing activity that generates splash droplets contacting worker skin.…”
Section: Methodsmentioning
confidence: 96%